‘Bilampau’: A Heritage – Long Forgotten (SIRJANĀ – A Journal Of Arts and Art Education, 2022)
Unlike some other forms in Nepali Painting, an earlier form known as ‘Bilampau’ remains unknown, relatively. This sense of apathy is regardless of the fact that this genre also boasts many unique features that deserves further academic explorations and need attract deeper discussions. To highlight its importance and explain the diversities, a few select representative examples are chosen to argue.As an earliest example, two painted wood-covers of sacred manuscripts dated 12th century are proffered, how early efforts were made to make a visual story in early medieval times. This is followed by a famous visual story based on Buddhist beliefs for telling Buddhist stories: and now, how it has been reduced to an annual display or as a mere ritual. A visual story of Lord Krishna remains yet one more example. It is created and based on Hindu epic Mahabharata. But the most unique and startling example cited herein has a very unique character. It is created as a visual travel guide or a suggestive map to a prospective pilgrim or a traveler. At present, this exquisite work is in the collection of a museum abroad.